Traditional masculinity, peer pressure, and sensation seeking as correlates of risky behaviours - Adugna Bersissa Merdassa (International Journal of Adolescence and Youth)
The relationship between traditional masculinity, peer pressure, sensation seeking and undergraduate students’ involvement in risky behaviours was examined using correlational research design. Results indicated higher levels of each predictor variable correlated significantly and positively with undergraduate students’ involvement in risk behaviours. Conformity to traditional masculinity contributed significantly to the variance in involvement in risky behaviours in the positive direction, and male undergraduate students involved more in risky behaviours than females. However, contributions of peer pressure and sensation seeking were non-significant. Traditional masculinities should be challenged and replaced by alternative positive masculinities in a country’s effort to fight against STIs, unplanned pregnancies, and abuse of alcohol and other substances.